Handling Panic Attacks in Abu Zaid Al-Balkhi's Mental Health Review - Bahaudin, Mohamad Saikhul; Ardi, Mulia (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
Mental health is one of the issues that has long been studied by Islamic civilization. As one of the early originators of mental health studies, al-Balkhi has contributed a lot through the book Mashalih al Abdan wa al Anfus. Panic and panic attacks are themes that appear quite often in the lives of modern people. According to data collected by Epidemiological studies, cases of panic disorder (PD) reach a range of 1.4 to 4.1% of the adult population. While panic attacks (PA) are in 14.4% of the population in countries that have high incomes. In addition, when compared to men, women have a higher potential of about 3-6% to suffer from the disorder. This research uses a library research method by collecting print and digital references and analyzing them with content analysis. According to al-Balkhi, panic, and panic attacks are interrelated conditions and are chronic forms of fear and anxiety. However, close or actual events are the most powerful drivers in triggering the disorder. Attempts to find meaning in events and redirect irrational thoughts towards something more rational are common themes in al-Balkhi's psychotherapy.